2012
DOI: 10.1186/1756-8722-5-29
|View full text |Cite
|
Sign up to set email alerts
|

Administration of imatinib after allogeneic hematopoietic stem cell transplantation may improve disease-free survival for patients with Philadelphia chromosome-positive acute lymphobla stic leukemia

Abstract: BackgroundMaintenance therapy with imatinib during the post-transplant period has been used for patients with Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph + ALL); however, its efficacy has not been demonstrated. A study was designed to investigate the safety of imatinib and its efficacy in preventing hematological relapse and improving disease-free survival (DFS) when administered after allogeneic hematopoietic stem cell transplantation (allo-HCT).MethodsPatients with Ph + ALL that receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 28 publications
3
76
1
Order By: Relevance
“…20 In addition, the decreased relapse rate may be owing to some preemptive strategies for preventing relapse, such as risk-stratified DLI 10 or low-dose IL-2, 8 which is administered at our center, and early prophylactic imatinib for Phpositive ALL patients after transplantation. 7,21 The toxicity of transplantation in previous studies may explain why a reduced relapse rate did not translate to improved survival. In the Medical Research Council and Eastern Cooperative Oncology Group study, the 5-year relapse rate was significantly lower in high-risk patients who received transplantations (donor vs no donor, 37% vs 63%, P o0.001).…”
Section: Discussionmentioning
confidence: 99%
“…20 In addition, the decreased relapse rate may be owing to some preemptive strategies for preventing relapse, such as risk-stratified DLI 10 or low-dose IL-2, 8 which is administered at our center, and early prophylactic imatinib for Phpositive ALL patients after transplantation. 7,21 The toxicity of transplantation in previous studies may explain why a reduced relapse rate did not translate to improved survival. In the Medical Research Council and Eastern Cooperative Oncology Group study, the 5-year relapse rate was significantly lower in high-risk patients who received transplantations (donor vs no donor, 37% vs 63%, P o0.001).…”
Section: Discussionmentioning
confidence: 99%
“…5 Our previous study demonstrated that patients treated with imatinib maintenance therapy guided by BCR-ABL monitoring by RQ-PCR after allo-HSCT have a lower estimated 5-year relapse rate (10.2%) compared with patients not treated with imatinib (33.1%). 3 However, challenges remain in implementing the experimentally validated biomarkers for recurrence prediction for risk-stratification therapy in Ph + ALL after allo-HSCT. In agreement with our previous report for de novoPh + ALL, 13 the novel CD34 + CD38 − CD58 − LPC phenotype has significant power to identify patients at high risk for relapse post HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] Imatinib treatment was scheduled for 3-12 months post HSCT, after the BCR-ABL transcript levels were negative for at least three consecutive tests or major molecular remission (MMR) was sustained for at least 3 months, as described in our previous report. 3 Minimal residual disease (MRD) assessment BCR/ABL transcript levels in BM samples were monitored at diagnosis; directly before transplantation; 1, 2, 3, 6, 9, 12, 24, 36 and 60 months post HSCT; and at relapse using RQ-PCR as previously described. 20,21 In patients with a 41log rising level of BCR/ABL transcripts, monitoring was performed every 2 weeks.…”
Section: Treatment Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies argue in favor of a maintenance therapy with imatinib after transplant in patients with a positive MRD evaluation, and this has also been suggested in more recent studies. 46,47 In contrast, Yanada et al 38 observed no association between rapid achievement of BCR-ABL1 negativity and long-term outcome after an initial imatinib/chemotherapy induction regimen, and the GRAAL group also reported that early MRD evaluation did not significantly influence patient outcome, either in terms of OS or DFS. 20 One issue that remains open to discussion concerning the role of MRD is represented by the substantial differences in the way PCR for BCR-ABL1 detection is performed, how results are reported in different laboratories worldwide, and the timing of MRD evaluation.…”
mentioning
confidence: 97%